THE INSPIRATION AND INTERPRETATION OF SCRIPTURE: WHAT THE EARLY CHURCH CAN TEACH US - C. Stenschke (Acta Theologica)
The following book is reviewed: Michael Graves (Grand Rapids, Cambridge, UK: Eerdmans, 2014). 201 pp., paperback. ISBN 978-0-8028-6963-0, 24 USD.